Fundamentals of light microscopy and electronic imaging - Murphy, Douglas B (Wiley-Liss, 2001)
Fundamentals of Light Microscopy and Electronic Imaging Douglas B. Murphy Over the last decade, advances in science and technology have profoundly changed the face of light microscopy. Research scientists need to learn new skills in order to use a modern research microscope–skills such as how to align microscope optics and perform image processing. Fundamentals of Light Microscopy and Electronic Imaging explores the basics of microscope design and use. The comprehensive material discusses the optical principles involved in diffraction and image formation in the light microscope, the basic modes of light microscopy, the components of modern electronic imaging systems, and the image processing operations necessary to acquire and prepare an image. Written in a practical, accessible style, Fundamentals of Light Microscopy and Electronic Imaging reviews such topics as: Illuminators, filters, and isolation of specific wavelengths Phase contrast and differential interference contrast Properties of polarized light and polarization microscopy Fluorescence and confocal laser scanning microscopy Digital CCD microscopy and image processing Each chapter includes practical demonstrations and exercises along with a discussion of the relevant material. In addition, a thorough glossary assists with complex terminology and an appendix contains lists of materials, procedures for specimen preparation, and answers to questions. Both experienced and novice microscopists will find Fundamentals of Light Microscopy and Electronic Imaging an essential resource.
Keywords: chemie, klinická chemie; mikroskopie; Microscopy